PENGARUH PENGGUNAAN GARAM NATRIUM DAN KALIUM METABISULFIT PADA MUTU SALE PISANG AMBON - ANNY SULASWATTY; ROESTAMSJAH ROESTAMSJAH (Research Center for Chemistry - LIPI, 1991)
Techniques of improving the colour, aroma, texture and storage life of pisang sale or dried banana (Musa paradisiacal was conducted through sulphiting and drying. In this study, the sulphiting of ball all a fruit was done by soaking the fruit in O.S% sodium meta bisulfite solution (NazSzOs) or O.S% potasium metabisulfite solution (K2S2O5) for five minutes. Dehydration was conducted at 6O°C for 44 hours in a tray dryer. The dried banana was put in plastic bag of O.5 mm film thickness and stored in a rack covered with transparent plastic film at ambient temperature (25° ± 2°C) and relative humidity of ±70%. The experiment was done using random block design. Analysis of the dried banana products included chemical, microbiological an d organoleptic methods after storage for one day, three weeks, six weeks and 12 weeks. The results indicated that the artificial drying coupled with the metablsulphite treatment could improve the quality and shelf life of the dried banan a produced. The product quality characteristics include: water content (23-27%), total reducing sugar (41-49%), SO2 (3-S fpm), color/optical density (0,3-0,7); and total colony count (7-7.5 x 10(3)) per gram sample for the products stored up to 12 weeks.